Analyzing Language-in-Education Policy at Vocational Institutions: A Case Study in Vietnam - Ho, Thi Quynh Nhu (Journal of Technical Education Science, 2023)
The project Teaching and studying foreign languages in the national educational system for the period 2008-2020 has prompted Vietnam's colleges and universities to innovate their language training programs. In this setting, the Project of Foreign Language Education at Hue Industrial College for the period 2012-2020 was born. The goal of this study is to examine this institution's language-in-education policy which is analyzed using the framework of the Baldauf and Kaplan’s (2005) planning goals. This paper specifies the author’s assessment of this vocational institution’s language policy on seven planning goals ranging from access policy, personnel policy, curriculum policy, methods and materials policy, resourcing policy to community policy. The study also suggests some pedagogical implications for Hue Industrial College's application of language teaching and learning practices and it was an attempt to provide more insights into the implementation of the Language-in-education Policy in orientation to the Vietnam National Project at other vocational institutions in Vietnam.